2009
DOI: 10.1590/s0074-02762009000500021
|View full text |Cite
|
Sign up to set email alerts
|

Identification of uropathogenic Escherichia coli clonal group A (CgA) in hospitalised patients

Abstract: This study provides the first description of healthcare-associated infections with (Manges et al. 2001, 2004, Johnson et al. 2002, Petrof et al. 2002. CgA isolation has also been described in other parts of the world (Johnson et al. 2005, Manges et al. 2008. The isolates in Latin America studied to date were found among a collection of 60 E. coli isolates of unknown origin in Curitiba, state of Paraná, Brazil. CgA was found in three urine isolates by random amplification of polymorphic DNA and phylogenetic gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
2
4
0
Order By: Relevance
“…Isolates belonging to cluster I seem to have been circulating among different continents since at least 1999, as reflects this and other studies [31-33]. Despite of the small sample analysed, differences among ST69 isolates from human and non-human origins suggest independent evolution of particular E .…”
Section: Resultssupporting
confidence: 83%
“…Isolates belonging to cluster I seem to have been circulating among different continents since at least 1999, as reflects this and other studies [31-33]. Despite of the small sample analysed, differences among ST69 isolates from human and non-human origins suggest independent evolution of particular E .…”
Section: Resultssupporting
confidence: 83%
“…Thus, we cannot exclude such isolate origins as possible reservoirs. The detection of CgA isolates from UTI patients also supported previous findings of a widespread global emergence of CgA isolates among uropathogenic E. coli (UPEC) (2,3,(10)(11)(12)(14)(15)(16)(17).…”
Section: Urinary Tract Infection (Uti) Is One Of the Most Common Bactsupporting
confidence: 86%
“…The possibility that the PFGE profiles of one community-dwelling human and two UTI isolates are related to the PFGE profile of the ATCC BAA-457 isolate is surprising considering the geographical distance and absence of any apparent epidemiological connections. However, other studies have likewise reported PFGE similarities of UTI isolates obtained in Chicago, IL, and Curitiba and Rio de Janeiro, Brazil, to the ATCC BAA-457 isolate (2,3,12). We have no explanation for this finding, but there is a possibility that the BAA-457 isolate belongs to an epidemic, broadly disseminated E. coli lineage.…”
Section: Urinary Tract Infection (Uti) Is One Of the Most Common Bactmentioning
confidence: 88%
See 1 more Smart Citation
“…In the United States, prevalence of MDR E. coli among community isolates increased more than 56% from the 1950s to the 2000s [1]. In Latin America, the widespread dissemination of phylogenetically related strains of uropathogenic E. coli in community and hospital settings has been observed and attributed to a common source in the community such as food and water or person-to-person transmission [16,17].…”
Section: Introductionmentioning
confidence: 99%